Reaksi Pasar Modal Terhadap Peristiwa Pemungutan Suara Dan Pengumuman Hasil Quickcount Pemilihan Presiden Dan Wakil Presiden Republik Indonesia Tahun 2019 - Revi Candra; Nasfizar Guspendri; Elfina Yenti (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The problem in this study is that the capital market is an economic instrument that is very vulnerable and sensitive to variables outside the company, such as information on economic, political, legal, social, and human rights policy issues, thus making the capital market react to this information, be it a positive reaction or a negative reaction. The motivation for this observation is the impact of political events in the form of capital market reactions through abnormal yield and trading volume activities.Research conducted on an event that occurs (Event Study) uses a quantitative descriptive approach by conducting a comparative study using the paired sample T-test. The capital market did not react to the Voting event and the announcement of the results for the Quick count 2019 presidential and vice presidential elections, because there were no differences in Abnormal Return and Trading Volume Activity before and after these events. The announcement of voting events and results for the 2019 Presidential and Vice Presidential elections in the Republic of Indonesia did not affect the stock index and stock trading volume of the Indonesia Stock Exchange. Keywords : Election of President and Vice President, quick count, Abnormal Return, Trading Volume Activity